Artificial Life 14: Proceedings of the Fourteenth International Conference on the Synthesis and Simulation of Living Systems 2014
DOI: 10.7551/978-0-262-32621-6-ch147
|View full text |Cite
|
Sign up to set email alerts
|

Steps Toward a Modular Library for Turning Any Evolutionary Domain into an Online Interactive Platform

Abstract: Natural evolution inspires the fields of evolutionary computation (EC) and artificial life (ALife). A prominent feature of natural evolution is that it effectively never ends. However, most EC and ALife experiments are only run for several days or weeks at a time. Once an experiment concludes, reproducing, observing, or extending the results often requires considerable effort. In contrast, some Collaborative Interactive Evolution (CIE) systems, e.g. Picbreeder, were designed to preserve results as potential st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In 1994, Karl Sims demonstrated that artificial evolution can produce novel morphology that resembles organisms observed in nature [59,60]. Subsequent works further investigated morphology evolution [4,8,9,11,37,44,64,65,70], modular robotics [39,45,48,75], and evolving soft robots [17,20], using indirect encoding [5,6,7,23,61].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1994, Karl Sims demonstrated that artificial evolution can produce novel morphology that resembles organisms observed in nature [59,60]. Subsequent works further investigated morphology evolution [4,8,9,11,37,44,64,65,70], modular robotics [39,45,48,75], and evolving soft robots [17,20], using indirect encoding [5,6,7,23,61].…”
Section: Related Workmentioning
confidence: 99%
“…In 1994, Karl Sims demonstrated that artificial evolution can produce novel morphologies that resemble organisms observed in nature [51,52]. Subsequent works further investigated morphology evolution [5,31,38,56,57,62], modular robotics [33,39,42,67], and evolving soft robots [11,14] using indirect encoding [17,53]. Theo Jansen [27] used evolutionary computation to design physical Strandbeests that can walk on their own consuming only wind energy.…”
Section: Related Workmentioning
confidence: 99%
“…Paul Szerlip and Ken Stanley are currently developing the Worldwide Infrastructure for Neuroevolution (WIN) project, which aims to provide a general-purpose solution that will greatly reduce the effort required to build such systems [124]. Also under development is an associated public web-based front end for ongoing experiments built with the WIN platform, called WIN Online.…”
Section: Worldwide Infrastructure For Neuroevolutionmentioning
confidence: 99%
“…It can be run from any browser without installation-embedded visualization is implemented using Google始s Chart API, 124 and the server side is implemented using a variety of modern technologies based on Java virtual machines ( JVMs). Without the need for installation, the authors argue that COEL has a larger potential audience than existing desktop-based systems.…”
Section: Coelmentioning
confidence: 99%
“…http://winark.org/, a proposed framework for turning any evolutionary domain into an online interactive platform[29]. The modules are compiled with the Component 3…”
mentioning
confidence: 99%